Distribución geográfica y caracteres poblacionales de Cupriguanus fasciatus (D'Orbigny) (Sauria Iguanidae) - Cei, José Miguel Alfredo María (1973)
Taxonomic position, ecology and populational features of Cupriguanus fasciatus (d’Orbigny) from Mendoza, Neuquén and Chubut Provinces of Argentina are analyzed. The homogeneous serological trends of several populations from Patagonian environments are pointed out. The striking similarity between young specimens from Chubut and d’Orbigny’s Type is reported.